Heterotopic gastric mucosa in the rectum - Sairvan Fernandes; Arash Safavi; Basile Tessier-Cloutier; Anna Lee; Robert Baird (Elsevier, 2020)
Heterotopic gastric mucosa is rare in the pediatric population. We present a case of a 14-year-old girl with a 6-month history of intermittent rectal bleeding and failed sclerotherapy. Excision ultimately demonstrated heterotopic gastric mucosa. This reports highlights that while most of the non-congenital pediatric anorectalpathology will continue to be hemorrhoids and prolapse, heterotopic gastric mucosa should be considered in patients with anorectal symptoms refractory to conventional treatment.